2022
DOI: 10.1186/s12885-022-09840-6
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II molecule HLA-DRA identifies immuno-hot tumors and predicts the therapeutic response to anti-PD-1 immunotherapy in NSCLC

Abstract: Background Immune checkpoint blockade (ICB) only works well for a certain subset of patients with non-small cell lung cancer (NSCLC). Therefore, biomarkers for patient stratification are desired, which can suggest the most beneficial treatment. Methods In this study, three datasets (GSE126044, GSE135222, and GSE136961) of immunotherapy from the Gene Expression Omnibus (GEO) database were analyzed, and seven intersected candidates were extracted as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…The activation status of TME infiltrates has been reported to influence the presence and functionality of tumor-reactive T cells [43][44][45][46] , a feature that was also reported for NSCLC 42,47 . PD-L1, which is expressed on activated immune cells, plays a key role in suppressing inflammatory immune responses 48 .…”
Section: Presence and Activation Status Of Neutrophils Negatively Cor...mentioning
confidence: 74%
“…The activation status of TME infiltrates has been reported to influence the presence and functionality of tumor-reactive T cells [43][44][45][46] , a feature that was also reported for NSCLC 42,47 . PD-L1, which is expressed on activated immune cells, plays a key role in suppressing inflammatory immune responses 48 .…”
Section: Presence and Activation Status Of Neutrophils Negatively Cor...mentioning
confidence: 74%
“…Recent studies have shown that reduced HLA-DRA correlated with a lower immune enrichment score of CD4 + T cells 43 and could predict the response to anti-programmed death-1 immunotherapy in NSCLC. 44 Furthermore, we examined the association of these prognostic genes with the drug sensitivity profiles of NSCLC chemotherapeutic drugs in 135 NSCLC cell lines. We found that prognostic genes showed significant differential expression in mRNA and protein level in sensitive vs. resistant NSCLC cell lines (2-sample t-tests; p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the abundance of tumor-infiltrating lymphocytes (TILs), TME can be classified into hot tumors (inflamed type) and cold tumors (desert and excluded type) [ 24 ]. Hot tumors generally exhibit richer immune infiltrations and better immunotherapy response than cold tumors [ 25 , 26 , 27 ], while poor TILs infiltrations are associated with immunotherapy resistance [ 28 , 29 ]. Thus, accurately distinguishing cold tumors from hot tumors can improve immunotherapy efficiency and reduce unnecessary medical costs.…”
Section: Discussionmentioning
confidence: 99%